TINJAUAN RUANG TERBUKA HIJAU RUMAH SUSUN DARI ASPEK PENATAAN DAN PENYEDIAAN - Has Fredrick T.H. Gultom; Monica Aryani (TATANAN, 2007)
Abstract                The green open space has a little bit attention in Jakarta, which has very dense of population and high temperature, especially in the high rise building environment; but actually the main function of that spaces is for cooling the environment and as the buffer of noise.                This study explored the ideal ordering and supplying green open spaces for the settlement especially for the low-cost apartment. The case study is about the green open space in the ten floors Bendungan Hilir low cost apartment, Jakarta. This analysis is to discovered the ideal condition of green open space in this apartment in order to the quantity of floors. The analysis based on the standards of the ordering and supplying green open space according to the literatures and the local regulations, so that the result can be used as determinant for improving the quality of ecological space in every area development effort.Keywords: green open space, low cost apartment, Bendungan Hilir JakartaAbstrak                Ruang terbuka hijau kurang mendapat perhatian di kota Jakarta yang sangat padat penduduk dan bertemperatur tinggi, terutama di lingkungan bangunan yang berlantai banyak; padahal fungsi utama ruang hijau tersebut adalah sebagai penghawaan lingkungan dan juga buffer terhadap bising.                Studi ini membahas tentang penataan dan penyediaan ruang terbuka hijau yang ideal untuk permukiman terutama untuk rumah susun. Kasus studi ini adalah tentang penataan dan penyediaan ruang terbuka hijau di rumah susun sepuluh lantai Bendungan Hilir, Jakarta. Analisis ini ditujukan untuk mengungkap kondisi ideal ruang terbuka hijau di rumah susun tersebut, apakah sehubungan dengan jumlah lantainya.                Analisis berdasarkan teori dari literatur dan peraturan-peraturan daerah setempat, sehingga hasilnya dapat dijadikan pertimbangan untuk meningkatkan kualitas ekologi ruang dalam setiap upaya pembangunan kawasan.Kata kunci: ruang terbuka hijau, rumah susun, Bendungan Hilir Jakarta